A review of the use of natural and chemical coagulants in turbidity removal of wastewater / Muhammad Farouk Muhamad, Ainnie Rahayu Abdullah and Dr. Norain Isa - Muhamad, Muhammad Farouk; Abdullah, Ainnie Rahayu; Isa, Norain (2020)
The introduction of natural materials into the coagulation-flocculation process need to be practiced as common as possible. The previous literature indicated that utilization of natural material is worth to be developed and if possible, into the commercial one. However, the application of natural coagulants itself as the primary treatment is not enough, due to the rise in constraints which limited its performance. Emerging technologies and depth studies are helping these limited conditions to grow them as good as the performance of chemical coagulants. Alternatively, the natural-based coagulants are commonly used as coagulant aids alongside chemical coagulants, which have created a highlight in water research. This review covers the comparison of type of coagulants used in the coagulation-flocculation of wastewater treatment in the usage of natural-based coagulants and chemical coagulants. This review paper also outlines the prospects of natural materials as aids and its potential as sustainable composite coagulants.